Karakterisasi Senyawa Caulersin, Caulerpol, Caulerpenyne dan Farocaulerpin Pada Alga Hijau (Caulerpa racemosa) dari Manggewa Pulau Mansinam Manokwari dengan Pendekatan Uji In Silico - Rumayomi, Esterlina; Wattimury, Dougklas; Hutasoit, Hostalige (Fakultas Teknologi Pertanian, Universitas Papua, Manokwari, 2024)
In some Asian cultures, C. racemosa is utilized through Traditional Medicine where it is used as a source of nutrition and is thought to have health benefits, including antioxidant and anti-inflammatory properties. One of them is treating digestive problems, which is carried out by several traditional medicine practices using C. racemosa to help overcome digestive problems or to improve intestinal health because of its fiber content. The bioactive compounds in Caulerpa racemosa play an important role, one of which is the compounds Caulersin, Caulerpol, Farocaulerpol and Caulerpenyne which are a group of compounds known as glucosinolates, which have various biological activities including the potential for health. This research method was carried out in an exploratory descriptive manner using an online database with the Windows 10 system, namely SwissADME, PubChem and PASSonline. The ingredients consist of 4 structures of C.racemosa bioactive compounds, namely: Caulersin, Caulerpol Farocaulerpol and Caulerpenyne which were obtained from the PubChem database. Based on research results, it shows that the bioactive compounds Caulersin and Caulerpol have the ability to act as hydrogen bond donors and acceptors, which shows that they are more polar and soluble in water, this has the potential to increase interactions with other molecules or proteins which can influence biological activity. Meanwhile, the absorption (GI Absorption) is only found in the compounds Caulersin, Caulerpol and Farocaulerpine, showing high absorption ability so that it can be absorbed well into the blood circulation after consumption. Overall compounds 1,2 and 3 showed good potential in terms of absorption, solubility and biological interactions. Meanwhile, the Caulerpenyne compound requires further research to understand its properties and capabilities.